Aflatoxina M1 no leite tipo "B" comercializado no Município de São Paulo, SP (Brasil) Aflatoxin M1 in B-type milk sold in S.Paulo city, Brazil - Jorge Luiz Seferin Martins; Ignez Salas Martins (Universidade de São Paulo, 1986)
No leite tipo "B", comercializado no Município de São Paulo, SP (Brasil), foi pesquisada a presença de aflatoxina M1. As amostras de leite analisadas foram provenientes das quatro marcas de maior consumo pela população, coletadas no período de julho a outubro de 1982. A aflatoxina M1, embora em baixos níveis e em pequena proporção (1,8%), fez-se presente nas quatro marcas. B-type milk sold in the city of S.Paulo, Brazil, was examined for Aflatoxina M1. Samples were taken from the four brands of greatest consumption in the period from June 14th through October 31th, 1982. Aflatoxin M1, although in small proportion (1.8%) and at low levels, was present in the brands studied.